A meta‐review of the impact of compression therapy on venous leg ulcer healing. Issue 2 (18th July 2022) - Patton, Declan; Avsar, Pinar; Sayeh, Aicha; Budri, Aglecia; O'Connor, Tom; Walsh, Simone; Nugent, Linda; Harkin, Denis; O'Brien, Niall; Cayce, Jonathan; Corcoran, Michael; Gaztambide, Mario; et al.
Abstract: This meta‐review aimed to appraise and synthesise findings from existing systematic reviews that measured the impact of compression therapy on venous leg ulcers healing. We searched five databases to identify potential papers; three authors extracted data, and a fourth author adjudicated the findings. The AMSTAR‐2 tool was used for quality appraisal and the certainty of the evidence was appraised using GRADEpro. Data analysis was undertaken using RevMan. We identified 12 systematic reviews published between 1997 and 2021. AMSTAR‐2 assessment identified three as high quality, five as moderate quality, and four as low quality. Seven comparisons were reported, with a meta‐analysis undertaken for five of these comparisons: compression vs no compression (risk ratio [RR]: 1.55; 95% confidence interval [CI] 1.34‐1.78; P  < .00001; moderate‐certainty evidence); elastic compression vs inelastic compression (RR: 1.02; 95% CI: 0.96‐1.08; P  < .61 moderate‐certainty evidence); four layer vs <four‐layer bandage systems (RR: 1.07; 95% CI: 0.82‐1.40; P  < .63; moderate‐certainty evidence); comparison between different four‐layer bandage systems (RR: 1.08; 95% CI: 0.93‐1.25; P  = .34; moderate‐certainty evidence); compression bandage vs compression stocking (RR 0.95; 95% CI 0.87‐1.03; P  = .18; moderate‐certainty evidence). The main conclusion from this review is that there is a statistically significant difference in healing rates when compression is used compared with no compression, with moderate‐certainty evidence. Otherwise, there is no statistically different difference in healing rates using elastic compression vs inelastic compression, four layer vs <four‐layer bandage systems, different four‐layer bandage systems, or compression bandages vs compression stockings.